Improving Indonesia's Commitment to Open Government Through Online Petition - Kusumaningrum, Adi; Bachtiar, Rizqi; Listiningrum, Prischa (Indonesian Journal of International Law, 2019)
Since 2011 Indonesia has joined as a member of Open Government Partnership, which is an international platform for countries committed to making their government more open, accountable, and responsive to citizens. However, the implementation of open government in Indonesia is criticized by some researchers because of the simplification of meaning. Open government is often described as uploading all government information into the official government website.Therefore, alternative policies are needed to ensure the openness of the government. This study offers the idea of ​​creating an online petition system officially administered by the House of Representatives as an alternative forum. The petition system offered is different from the conventional online petition system, because the conventional system does not have clear legal umbrella and is managed by Non-Governmental Organizations. By comparing the advantages and disadvantages of the addition of the authority to the Parliament, it is expected that the system will strengthen the oversight function by the Parliament. Nevertheless, the alternative solution offered in this study is highly dependent on the political will of the government and the House of Representatives in making clear and legal rules.